2013
DOI: 10.1007/s12032-012-0438-y
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulated expression of Notch signaling molecules in human endometrial cancer

Abstract: Notch signaling pathway is a highly conserved developmental pathway, which plays an important role in the regulation of cellular proliferation, differentiation and apoptosis. Deregulation of Notch pathway has been connected with the carcinogenesis in a variety of cancers. In this study, we investigated the expression of Notch receptors (NOTCH1, NOTCH2, NOTCH3 and NOTCH4), ligands (JAG1, JAG2 and DLL1) and target gene HES1. Fifty paired samples of endometrial cancer and adjacent nontumor endometrial tissue from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 21 publications
1
32
1
2
Order By: Relevance
“…20 As an example, the downregulation of Notch signaling inhibits the growth, migration, and invasiveness of cancer cells and induces cell apoptosis . 21 In the current study, we found that Notch signaling was expressed in both CD133C and CD133-cells. However, compared with CD133-cells, the expression in CD133C cells was higher.…”
Section: Discussionmentioning
confidence: 48%
“…20 As an example, the downregulation of Notch signaling inhibits the growth, migration, and invasiveness of cancer cells and induces cell apoptosis . 21 In the current study, we found that Notch signaling was expressed in both CD133C and CD133-cells. However, compared with CD133-cells, the expression in CD133C cells was higher.…”
Section: Discussionmentioning
confidence: 48%
“…The idea of downregulation of Notch signaling is novel for lung cancer but it is not unexpected in the light of studies performed on other types of cancer, including endometrial cancer. Jonusiene et al (24) investigated the expression of Notch receptors (Notch 1, Notch 2, Notch 3 and Notch 4), ligands (Jag1, Jag2 and Dll1) and target gene Hes1 in endometrial cancer and adjacent non-tumor endometrial tissue from endometrial cancer patients. The mRNA levels of Notch receptors and ligands were reduced in endometrial cancer compared with adjacent non-tumor tissue (24).…”
Section: Discussionmentioning
confidence: 99%
“…Jonusiene et al (24) investigated the expression of Notch receptors (Notch 1, Notch 2, Notch 3 and Notch 4), ligands (Jag1, Jag2 and Dll1) and target gene Hes1 in endometrial cancer and adjacent non-tumor endometrial tissue from endometrial cancer patients. The mRNA levels of Notch receptors and ligands were reduced in endometrial cancer compared with adjacent non-tumor tissue (24). Furthermore, in contrast to the results of the present study, the expression of Notch1, Notch4 and Dll1 in IB stage adenocarcinoma was significantly reduced compared with the expression of these molecules at the IA stage (16).…”
Section: Discussionmentioning
confidence: 99%
“…Mūsų su bendraautoriais atliktų tyrimų, kuriuose nagrinėta gimdos kūno vėžio bei NOTCH signalinio kelio sąsaja, duomenys paskelbti dviejose publikacijose (33,34). Tyrimams naudoti 50 pacienčių mėginiai (tirtas kiekvienos pacientės navikinis ir sveikas endometriumo audinys), gauti operacijos metu pašalinus gimdą.…”
Section: Notch Signalinio Kelio Vaidmuo Formuojantis Gimdos Kūno Vėžiuiunclassified